Mucuna pruriens (Konch Beej) precipitates manic symptoms - Supriya Vaish; Sachin Sharma; S Sudarsanan; S Choudhary; Jai Meher Singh; Nafroz Khosla (Journal of Mental Health and Human Behaviour, 2014)
Owing to the popular misconception that all ayurvedic preparations are completely safe, a vast majority of these are indiscriminately consumed by people procured as over the counter drugs. These preparations are combinations of multiple products that are often unidentified and dangerous and can precipitate various psychiatric symptoms. Hereby, we present a case of adolescent male in acute manic excitement after consumption of ayurvedic preparation containing "konchbeej" (Mucuna pruriens) which is rich in l-3,4 dihydroxyphenyl alanine; precursor of dopamine.